Renewable Energy Consumption: the Effects on Economic Growth in Mexico - Mele, Marco (International Journal of Energy Economics and Policy, 2019)
This study will demonstrate, through an econometric approach, the renewable energy consumption-economic growth effects in Mexico over the period 1990-2017. After a premise where we describe the situation of energy demand and consumption in Mexico and a summary of the economic literature, we have applied various econometric tests. Results about unit root tests describe a situation with all variables that aren’t stationary except that in first differences. The Toda and Yamamoto approach is very important in our analysis: it highlights the existence of a unidirectional causal flow, running from renewable energy consumption to aggregate income. This situation respects the theory and hypothesis of economic growth. Keywords: Renewable Energy Consumption, Economic Growth, Causality, Mexico JEL Classifications: B22, C32, N54, Q43 DOI: https://doi.org/10.32479/ijeep.7460